“Collective Awareness Platform to enhance Social Media education in parents, children and teenagers” - Aguilar-Pérez, Tamara (My University, 2015)
El TFM se basa en la redacción de una propuesta europea destinada a la creación de una plataforma de concienciación social para educar a padres e hijos en el buen uso de las redes sociales. La plataforma englobará un sistema capaz de monitorizar, capturar datos y procesas datos en tiempo real.Se ha tomado de referencia la convocatoria ICT-2013.5.5 CollectiveAwarenessPlatformforSustainability and Social Innovation. Se han aplicado las metodologías y conocimientos adquiridos en las distintas asignaturas del Master, con el fin de obtener una propuesta lo más real posible a la realidad y poderla utilizar en mi carrera profesional.
Final Master Project is based on writing a European proposalaimed at creating a collective awareness platform to educate parents and children on the correct use of social media.The platform includes a system capable of monitoring, capture and analyzes data in real time. Reference has been made from theCall: ICT-2013.5.5 Collective Awareness Platform for Sustainability and Social Innovation. Writing this proposal has been a good opportunity to apply methodologies and knowledge acquired in the Master, in order to obtain a real proposal and useful for my professional career.
Keywords: seguridad; protección; redes sociales; educación; infancia; proyectos tecnológicos; Máster en Diseño y Gestión de Proyectos Tecnológicos